Mapping the location of grafted PNIPAAM in mesoporous SBA-15 silica using gas adsorption analysis. - Reichhardt, Nina Viola; Guillet-Nicolas, Remy; Thommes, Matthias; Klosgen, Beate; Nylander, Tommy; Kleitz, Freddy; Alfredsson, Viveka (Physical Chemistry Chemical Physics, 2012)
The thermoresponsive polymer poly-N-isopropylacrylamide (PNIPAAM) was grafted in mesoporous SBA-15 silica. The grafting process consists of three steps: (i) increasing the amount of surface silanol groups of SBA-15 by hydroxylation, (ii) attachment of an anchor (1-(trichlorosilyl)-2-(m/p-(chloromethylphenyl)ethane) and finally (iii) the polymerization of the monomers (NIPAAM) onto the anchor. After each step, the materials were characterized regarding the porosity, using inert gas (argon, nitrogen) physisorption measurements. Also, the structure was investigated by small-angle X-ray diffraction analysis and thermogravimetric analysis was used for determination of the amount of grafted material. A total of 17% by weight of organic material was introduced in the porous host and the structure was preserved during the grafting process. Physisorption measurements revealed that the anchor is mainly located in the intrawall pores present in SBA-15. Consequently, the polymer is preferentially located in the intrawall pores or in the vicinity thereof. The final mesopore volume is 0.47 cm(3) g(-1) as compared to 0.96 cm(3) g(-1) for the pure SBA-15. The surprisingly large loss of mesopore volume and an almost constant mesopore diameter is consistent with a partial sealing of the mesopore volume in the composite materials. The potential thermocontrol combined with the large mesoporosity and the possible "storage space" provided by the sealed mesopore volume leads to a material with possibilities for various applications.